2018
DOI: 10.1002/elan.201800032
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Aluminium Doped TiO2 Nanoparticles‐modified Screen Printed Carbon Electrode for Electrochemical Sensing of Vanillin in Food Samples

Abstract: A new chemically modified electrode based on titanium dioxide nanoparticles (TiO2‐NPs) has been developed. Aluminium was incorporated into the TiO2‐NPs to prepare aluminium doped TiO2 nanoparticles (Al‐TiO2‐NPs). Aluminium doped TiO2 nanoparticles‐modified screen printed carbon electrode (Al‐TiO2‐NPs/SPCE) was employed as easy, efficient and rapid sensor for electrochemical detection of vanillin in various types of food samples. Al‐TiO2‐NPs were characterized by energy‐dispersive X‐ray (EDX), transmission elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…MIPs were ultrasonically dispersed in pure water (with 0.5% Nafion, v : v ), and the concentrations of 1 mg mL −1 were obtained individually. The SPCE forming a layer of thin films from nafion-solubilized MIP are more uniformly distributed than those casted by organic solvents [ 21 , 22 ]. Then, 6 µL of the dispersed MIP was casted onto the surface of the SPCE.…”
Section: Methodsmentioning
confidence: 99%
“…MIPs were ultrasonically dispersed in pure water (with 0.5% Nafion, v : v ), and the concentrations of 1 mg mL −1 were obtained individually. The SPCE forming a layer of thin films from nafion-solubilized MIP are more uniformly distributed than those casted by organic solvents [ 21 , 22 ]. Then, 6 µL of the dispersed MIP was casted onto the surface of the SPCE.…”
Section: Methodsmentioning
confidence: 99%
“…The modification of the surface of electrodes by various organic and inorganic materials has long been an important area of the applied and theoretical researches . Modifiers such as polymers , various metal nanoparticles , multiwalled carbon nanotubes , boron‐doped diamond , graphene and its derivatives . Triazole and its derivatives as modifier compounds have attracted more interest due to their antimicrobial and antitumor properties.…”
Section: Introductionmentioning
confidence: 99%
“…In the electrochemical determination of vanillin, various types of electrodes and modified electrodes have been successfully used. For example, gold nanoparticlemodified screen-printed carbon electrode modified with graphene quantum dots and Nafion [12], overoxidized poly(pyrrole) film-modified glassy carbon electrode [13], Aluminum doped TiO2 nanoparticles-modified screen printed carbon electrode [14], AuPd nanoparticlesgraphene composite modified electrode [23] and screen printed graphite electrode [26] have been used for the determination of vanillin using differential pulse or square wave voltammetric techniques. However, our literature search showed that recently often preferred pencil graphite electrode (PGE) has not been used for the determination of vanillin.…”
Section: Introductionmentioning
confidence: 99%
“…In the determination of vanillin a variety of methods have been developed using chromatographic [5][6][7][8], spectroscopic [3,9,10] and electroanalytical techniques [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Although chromatographic methods such as GC and HPLC with various detectors (especially MS detector) have been widely used for the selective and reliable detection of vanillin [5][6][7][8], they have some drawbacks such as time consuming sample pretreatment procedures, high cost, expensive devices, high consumption of organic solvent, needs highly trained personal etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation